2007
DOI: 10.1007/s10603-007-9049-y
|View full text |Cite
|
Sign up to set email alerts
|

Illusory Price Increases after the Euro Changeover in Germany: An Expectancy-Consistent Bias

Abstract: Price perception, Judgmental bias, Prior belief effect, Expectancy confirmation, Selective outcome correction,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
(47 reference statements)
2
5
0
Order By: Relevance
“…Our findings indicate that global and undifferentiated expectations may play an important role in the perception of inflation. In line with our findings, some studies have shown that the perception of price increases as a result of the introduction of the euro was strongly influenced by expectations (Greitemeyer et al, 2005;Traut-Mattausch, Greitemeyer, Frey, & Schulz-Hardt, 2007;Traut-Mattausch et al, 2004). On the other hand, a recent line of research dealing with the perception of inflation (Brachinger, 2008;Jungermann, Brachinger, Belting, Grinberg, & Zacharias, 2007) did not consider expectations as a driver of perceived inflation, but used prospect-theoretical assumptions (Kahneman & Tversky, 1979) and the availability heuristic (Tversky & Kahneman, 1991) to explain why people tend to overestimate inflation.…”
Section: Theoretical Implicationssupporting
confidence: 87%
“…Our findings indicate that global and undifferentiated expectations may play an important role in the perception of inflation. In line with our findings, some studies have shown that the perception of price increases as a result of the introduction of the euro was strongly influenced by expectations (Greitemeyer et al, 2005;Traut-Mattausch, Greitemeyer, Frey, & Schulz-Hardt, 2007;Traut-Mattausch et al, 2004). On the other hand, a recent line of research dealing with the perception of inflation (Brachinger, 2008;Jungermann, Brachinger, Belting, Grinberg, & Zacharias, 2007) did not consider expectations as a driver of perceived inflation, but used prospect-theoretical assumptions (Kahneman & Tversky, 1979) and the availability heuristic (Tversky & Kahneman, 1991) to explain why people tend to overestimate inflation.…”
Section: Theoretical Implicationssupporting
confidence: 87%
“…A generalization from this research is that the bias in perceived inflation after the euro changeover in Germany is caused by the fact that expectation-consistent information is less critically assessed than expectation-inconsistent information. In line with this, Traut-Mattausch et al (2007) demonstrate that incorrect conversions from euro to the old currency that are perceived as price increases are not corrected whereas incorrect conversions perceived as price decreases are corrected. This error-correction mechanism is shown to lead to the observed bias in perceived price changes.…”
Section: Consumers' Understanding Of Price Changes In Eurosupporting
confidence: 61%
“…Based on frequent and reliable price checks, preferably taking into account the actual spending by different segments of citizens (Jungermann et al 2007), official sources may provide effective counterarguments. As noted by Traut-Mattausch et al (2007), counterarguments have been shown to be an effective means of debiasing. The error-correction mechanism proposed by these authors to account for the misperception of price changes may also depend on invested effort.…”
Section: Implications For Consumer Policymentioning
confidence: 99%
See 1 more Smart Citation
“…; Kooreman, Faber and Hofmans ; Cannon and Cipriani ; Gamble ); compression effect (Marques ); illusionary price effect (Traut‐Mattausch et al . , ); and emotional attachment effect (Tyszka and Przybyszewski ). Somewhat more closely related to the asymmetric price effect explored in our study, a number of studies focus on the imperfect information and confusion that may affect prices during currency substitution.…”
mentioning
confidence: 99%